Cognitive Counseling Intervention to Overcome Students’ Internet Addiction in Indonesian Vocational High Schools - Abdul Saman; Muhammad Arifin Ahmad; Muhammad Ilham Bakhtiar; Hadi Pranoto; Muhammad Anas (Journal of Educational Science and Technology (EST), 2021)
This research aims at identifying cognitive counseling intervention models to overcome students’ internet addiction at the Vocational High School Makassar. Besides, this study aims at determining the effectiveness of cognitive counseling to overcome students’ internet addiction at the Vocational High School Makassar. The research method was an experiment using the pretest-posttest control group design. The samples were 60 students divided into two groups, namely 30 experimental groups and 30 control groups. The data were collected data using the questionnaire. The data were then analyzed using descriptive analysis to obtain an overview of the level of students’ internet dependence before and after giving cognitive counseling interventions. The hypotheses were tested using t-test. There are some results in this study. First, the description of internet use behavior shows that there are indications that students are addicted to using the internet. It can be seen based on the time in accessing the internet, the objects used, and the types accessed when they use the internet. The level of internet addiction of students is in the high category. Second, the implementation of cognitive counseling interventions has a significant effect on decreasing the level of internet addiction. It is evident from the results of the posttest in the experimental group, which is lower than the control group. Third, the cognitive counseling intervention is effective to reduce students’ internet addiction of the Vocational High School Makassar.